Clockwork precision: egg-laying-induced rise of body temperature is seasonally programmed in a wild bird - Guillemette, Magella; Seyer, Yannick; Viain, Anouck (Frontiers in Physiology, 2024)
There is long time interest about the phenology of plants and animals living in seasonal environments as research in that field would help to understand the coping mechanisms leading to a higher fitness. For instance, it has been shown several decades ago that birds prepare themselves 2–4 months before the actual start of the breeding season by slowly growing reproductive organs. In parallel, the resting metabolic rate increase during reproduction in various vertebrates including mammals, reptiles, and birds. Recently, it has been reported that body temperature of a marine bird species was reaching an annual peak during egg-laying, raising the question about the seasonal dynamic of this important physiological feature. Using data loggers implanted in the abdominal cavity of female Common Eiders (Somateria mollissima mollissima) for a full year, we show here that daily body temperature (Tb.daily) is slowly increasing first and then accelerating at the approach of the laying period. Because the rise of Tb.daily is tightly associated with egg-laying in this species, we also analysed the influence of ambient temperature (water and air) and photoperiod on this seasonal dynamic. Based on the various mechanisms at work and a parsimonious interpretation of the data, we conclude that photoperiod is the main cue driving the seasonal breeding program of eiders. Although the laying dates of the instrumented females were highly clustered over a period of 4 years, we speculated that the remaining variation observed was the result of eco-physiological challenges occurring over the years.